Age factors: A view of the effect on SLA - Suhaimi, Suhaimi (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri (IAIN) Kerinci, 2016)
There are many differences among second language learners. In first language acquisition by children, individual differences (e.g. across genders or the language being learned) are largely overshadowed by striking similarities in terms of natural stages and ultimate attainment. However, in second language acquisition, individual differences have more of an impact on the second language learning process, and their role has thus received considerable attention in recent years. Learners beliefs and affective factors are likely to have a direct effect on second language learning, but they themselves may be influenced by a number of general factors relating to learners ability and desire to learn and the way they choose to go about learning. One of those important areas of difference among second language learners is age. We now turn to a discussion of four main effects of age on second language acquisition.